Advancements of nature nanocage protein: preparation, identification and multiple applications of ferritins. Issue 25 (1st September 2022) - Li, Han; Xia, Xiaoyu; Tan, Xiaoyi; Zang, Jiachen; Wang, Zhenyu; EI-Seedi, Hesham R.; Du, Ming
Abstract: Ferritin is an important iron storage protein, which is widely existed in all forms of life. Ferritin can regulate iron homeostasis when iron ions are lacking or enriched in the body, so as to avoid iron deficiency diseases and iron poisoning. Ferritin presents a hollow nanocage, which can store ions or other small molecular substances in the cavity. Therefore, ferritin shows its potential as a functional nanomaterial that can deliver nutrients or drugs in a targeted manner to improve bioavailability. Due to the special structure, the research on ferritin has attracted more and more attention in recent years. In this paper, the structural characteristics of ferritin were introduced, and the natural purification and prokaryotic expression methods of ferritin from different sources were described. At the same time, ferritin can bind to small molecules, so that it has the activity of small molecules, to construct a new type of ferritin. As a result, ferritin plays an important role as a nutrient substance, in targeted transport, and disease monitoring, etc. In conclusion, the yield of ferritin can be improved by means of molecular biology. Meanwhile, molecular modification can be used to make ferritin have unique activity and function, which lays a foundation for subsequent research. Highlights: The molecular and structural properties of ferritins were clearly described. Isolation and purification technologies of ferritin were compared. Characterization, functions and molecular modifications mechanism of ferritin were reviewed. The applications of ferritin in pharmaceutical and food industry were prospected.